Trace Elements in Feathers and Eggshells of Two Tropical Seabirds from Malaysia - Hamza, Abdulmaula; Hisham, Alya Syakirin; Suratman, Suhaimi; Bidai, Joseph Anak; Shazili, Noor Azhar Bin Mohamed (Marine ornithology, 2021)
Seabird feathers and eggshells are used as bio-monitors for trace metal contamination. Eleven trace element concentrations in wing primaries (n = 21) and eggshells (n = 8) are reported herein for two resident seabirds, Bridled Tern Onychoprion anaethetus and Black-naped Tern Sterna sumatrana, at Pulau Ling and Pulau Tokung Burung, Malaysia. Metal concentration followed the pattern Zn > Cr > Mn > Sr > Cu > Se > Ba > Pb > Cd > Ga > Li. Significant positive correlations existed among all trace metals, except for Cr in Black-naped Tern and Li and Cd in Bridled Tern feathers. We also analyzed metal concentrations in eggshells, and for Bridled Tern the concentration pattern was Zn > Mn > Se > Sr > Ba > Pb > Co > Cu > Cd, whereas for Black-naped Tern it was Cr > Zn > Mn > Ba > Sr > Se > Cu> Co > Pb. A pairwise positive correlation was significant among most trace metals in feather samples, indicating synergistic effects of two or more elements. More studies are needed to build a baseline database of trace metal concentrations in seabirds of Southeast Asia, as little research on this subject has been conducted in this region.